Exploring zakat payment intentions using the Theory of Planned Behavior among members of Muhammadiyah in Indonesia - Syaputra, Ahmad Danu; Ardiansyah, Misnen; Sa'adah, Nurus (Universitas Islam Indonesia, 2025)
IntroductionZakat plays a fundamental role in promoting economic justice and social welfare in Muslim communities. Muhammadiyah, as one of the largest Islamic organizations in Indonesia, actively manages zakat through its philanthropic institution. Despite this, zakat compliance remains uneven, prompting the need to understand what drives individuals' intentions to pay zakat within religious organizations.ObjectivesThis study aims to analyze the behavioral intentions to pay zakat among members of the Muhammadiyah organization. It specifically examines how attitude, subjective norms, and perceived behavioral control influence the intention to pay zakat, using the Theory of Planned Behavior as the guiding framework.MethodA quantitative approach was employed with a structured online questionnaire distributed to 200 members of Muhammadiyah. The data collected were analyzed using Structural Equation Modeling with the Partial Least Squares method to assess the relationships between the three behavioral constructs and zakat intention.ResultsThe findings reveal that perceived behavioral control and subjective norms significantly influence the intention to pay zakat among Muhammadiyah members. Perceived behavioral control emerged as the strongest predictor, indicating that the ability and convenience to pay zakat play a critical role. Subjective norms also had a notable positive impact, suggesting that social expectations and religious community influence enhance zakat intention. Contrary to common assumptions, attitude did not have a significant effect on behavioral intention in this context. The model explained 49 percent of the variance in zakat intention, demonstrating a moderate level of predictive power.ImplicationsThese results suggest that increasing zakat compliance in Islamic organizations such as Muhammadiyah requires strategies that enhance accessibility and social reinforcement. Strengthening the influence of religious leaders, promoting collective obligations, and improving ease of payment through institutional services can foster a stronger intention to fulfill zakat.Originality/NoveltyThis study contributes to the literature by applying the Theory of Planned Behavior to a specific religious organizational context. It provides new insights by highlighting that perceived control and normative influence are more decisive than individual attitudes in shaping zakat behavior among committed Muslim communities. This research offers a valuable reference for designing effective zakat campaigns and improving philanthropic engagement in Islamic institutions.